Nanoemulsion Formulation as a Drug Delivery System for Coleus atropurpureus Bioactive Compounds - Oktavioni, Marsella; Natasya, Dian; Yusnaidar, Yusnaidar; Latief, Madyawati; Tarigan, Indra L. (Universitas Padjadjaran, Indonesia, 2024)
Miana plant (Coleus) is a plant with compound flowers. Miana leaves have various bioactive compounds widely used to treat diseases such as fever, cold, cough, headaches, asthma, constipation, and skin diseases. Based on phytochemical screening of Coleus atropurpureus Benth. Several bioactive compounds are produced, such as sterols, terpenoids, alkaloids, phenols, flavonoids, glycosides, lactones, catechols, and tannins. Miana leaf extract has been tested for antioxidants using the DPPH method, and the IC50 value obtained from the antioxidant test results is 3.80 ppm and is categorized as a powerful antioxidant. There were four formulations of miana leaf extract nanoemulsion. Based on the characterization on the Miana leaf extract nanoemulsion preparation, formulations with good results were obtained in F1 and F3 with precise results and high transmittance values. In testing the miana leaf extract nanoemulsion, an organoleptic test was carried out on each formulation. It was found that all formulations had a distinctive smell of miana leaves, and no phase separation occurred, with the clarity of F1 and F3 classified as straightforward but F2 and F4 not clear, and the resulting color increased from F1 -F4. Meanwhile, for the physicochemical test, an O/W type nanoemulsion was produced, physically stable, with a particle size of F1 153.9 nm and F3 795.6 nm, with a zeta potential of F1 of 16.4 and F3 of -28.266.